The Evolutionary Course of Theory of Mind – Factors that facilitate or inhibit its operation & the role of ICTs - Bamicha, Victoria; Drigas, Athanasios (Technium Social Sciences Journal, 2022)
The Theory of Mind is a bridge of mental understanding between us and others. Its proper functioning provides opportunities for communication, effective social interaction, development on a cognitive and metacognitive level. The present study aims to examine its developmental stages from infancy to adolescence, as well as the main factors that stimulate or defeat its course. The crucial development of executive skills, language function, and the importance of the role of ICTs is pointed out, as they compensate for the difficulties in the formation of Theory of Mind and promote its continuous improvement throughout an individual's life.